Das Mythem der Verlorenen Sonnenstraheln und das Motiv des Rinderdiebstahls - Jagiełło, Mieszek (Polskie Towarzystwo Filologiczne, 2021)
This paper explores the relations between the mythological figures of the Rigvedic Saramā, Greek Hermes, Odysseus and Herakles. Core features of their respective mythological and literary narratives seem to suggest a common origin. Most intriguing is the fact that all four appear in connection to the “cattle of the sun” motif. In order to compare the relevant myths, an approach is hosen that allows to differentiate between the relevant mytheme and the motif.